2014
DOI: 10.1002/2014jd021577
|View full text |Cite
|
Sign up to set email alerts
|

The role of aerosol absorption in driving clear‐sky solar dimming over East Asia

Abstract: Surface-based observations indicate a significant decreasing trend in clear-sky downward surface solar radiation (SSR) over East Asia since the 1960s. This "dimming" is thought to be driven by the region's long-term increase in aerosol emissions, but little work has been done to quantify the underlying physical mechanisms or the contribution from aerosol absorption within the atmospheric column. Given the distinct climate impacts that absorption-driven dimming may produce, this constitutes an important, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 95 publications
2
13
0
1
Order By: Relevance
“…However, AERONET does show a peak in absorption AOD in March, with high year-to-year variation (large error bar) as well as a drop in both SSA and α. This is consistent with conclusions by Pietruczuk and Chaikovsky (2012) that dust is transported to Europe from the Saharan desert during spring. As shown before on a regional scale, CM3 improved the magnitudes considerably, but the seasonality deteriorated.…”
Section: Evaluating Model-derived Data With Spatially Collocated Instsupporting
confidence: 93%
See 2 more Smart Citations
“…However, AERONET does show a peak in absorption AOD in March, with high year-to-year variation (large error bar) as well as a drop in both SSA and α. This is consistent with conclusions by Pietruczuk and Chaikovsky (2012) that dust is transported to Europe from the Saharan desert during spring. As shown before on a regional scale, CM3 improved the magnitudes considerably, but the seasonality deteriorated.…”
Section: Evaluating Model-derived Data With Spatially Collocated Instsupporting
confidence: 93%
“…Analyses of back trajectories computed using the NOAA HYSPLIT (Hybrid Single Particle Lagrangian Integrated Trajectory Model) model and fire maps show that these peaks coincide with seasonal biomass burning in Eastern and Southern Europe (Jaroslawski and Pietruczuk, 2010). Another study uses lidar measurements and model results to suggest that transport of Saharan dust also influences springtime AOD in Belsk (Pietruczuk and Chaikovsky, 2012). This is consistent with CM2.1 (and not CM3), which shows a maximum absorption AOD, minimum SSA, and minimum Ångström exponent during March-April-May, as well as a peak in the dust AOD in May.…”
Section: Evaluating Multiple Aerosol Parameters In Polluted Regionssupporting
confidence: 55%
See 1 more Smart Citation
“…Several studies attempted to contrast the SO 4 and BC responses and indicated that scattering and absorbing aerosols would have markedly different effects on regional temperature, atmospheric circulation, and precipitation over East Asia (e.g., Guo et al, 2013;Jiang et al, 2013;Persad et al, 2014). However, these studies all only considered the fast adjustments of atmosphere and land surface to aerosol forcings, without considering the response of oceans.…”
Section: Introductionmentioning
confidence: 99%
“…They affect the amount of short wave radiation that reaches the ground through scattering and absorption, and also modify cloud properties, often described as having direct and indirect effects on climate (Tanré et al 1984;Charlson et al 1992;Kaufman and Nakajima 1993;Huang et al 2006;Persad et al 2014). Understanding the aerosol feedback on climate is difficult since aerosol composition, shape and size vary greatly with space and time .…”
Section: Introductionmentioning
confidence: 99%